Updating the healthcare maintenance visit for children with medical complexity: applying lessons learned from the coronavirus disease 2019 pandemic. Issue 2 (7th April 2022) - Driansky, Allison; Pilapil, Mariecel; Mastrogiannis, Ariana
Abstract : Purpose of review: Coronavirus disease 2019 (COVID-19) has exposed the vulnerabilities of children with medical complexity (CMC). This article uniquely describes how pediatric providers in various clinical settings can adapt routine healthcare maintenance visits to meet the needs of CMC in the era of COVID-19. We also discuss unique visit components important to address when providing primary care to CMC, including caregiver support, disaster preparedness, long-term care planning, and telemedicine. Recent findings: Although some children may be less severely affected by COVID-19 than adults, current literature suggests that CMC may be at higher risk for severe disease. In addition, the COVID-19 pandemic has highlighted the value in consistent, primary care for CMC. Children, especially those with medical complexity, are at risk for interruptions in care, delayed vaccinations, increasing caregiver burden, and barriers to in-person care. Summary: This article summarizes the components of the healthcare maintenance visit for CMC, providing salient recommendations on how pediatric providers can adapt their approach to the primary care of CMC in the era of COVID-19.